Merger remedies in oligopoly under a consumer welfare standard - Markus Dertwinkel-Kalt; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
We analyze the welfare effects of structural remedies on merger activity in a Cournot oligopoly if the antitrust agency applies a consumer surplus standard. We derive conditions such that otherwise price-increasing mergers become externality-free by the use of remedial divestitures. In this case, the consumer surplus standard ensures that mergers are only implemented if they increase social welfare. If the merging parties can extract the entire surplus from the asset sale, then the socially optimal buyer will be selected under a consumer standard.
Keywords: L13; L41; K21; 330; Remedies; Merger control; Consumer standard; Synergies